USE OF CORPORATE ACCOUNTING AND CONTROL SYSTEM IN MANAGEMENT - T. M. Rogulenko; A. V. Bodyko (Вестник университета)
The issues of formation of accounting and control system as a tool of corporate governance, information and analytical support of management goals have been examined. The principles and bases of its formation for tactical and strategic goals of business management have been defined. According to the results of the study a conclusion has been made, that the corporate accounting and control system is one of the modern algorithmized and automated tools of the corporate management system of economic development strategy in a highly competitive environment and the unpredictability of the behavior of economic entities in the market of goods, works, services, currency, securities, etc., which is integrated with other management systems in the mode of their parallel automation.